Teacher Identity Disclosure: Exploring Professionalism, Pedagogy, And Impact on Students in The Merdeka Mengajar Platform - Afina Fika Rahma; Junaidi Mistar; Sonny Elfiyanto; Subarjo (Ethical Lingua: Journal of Language Teaching and Literature, 2026)
This study investigates the role of the Merdeka Mengajar Platform (PMM) in shaping teacher identity and its impact on professionalism, pedagogical practices, and student learning outcomes among English teachers at secondary schools. Employing a qualitative phenomenological design, data were collected through semi-structured interviews and classroom observations with three teachers actively engaged in PMM. The findings reveal that PMM strengthens teachers’ professional identity by providing structured guidance, mentoring, and collaborative opportunities, which enhance confidence and resilience. In terms of pedagogy, the platform encourages a shift from teacher-centered to student-centered approaches, including project-based learning, peer feedback, digital storytelling, and role-play, thereby fostering innovation and active student engagement. Furthermore, PMM contributes to professional growth by motivating continuous learning and experimentation, while simultaneously improving student outcomes through increased motivation, confidence, and participation. Overall, PMM functions not only as a technological resource but also as a professional ecosystem that bridges teacher development with student success, offering significant implications for the advancement of English language education in Indonesia.